Quase famosos: Estudo de caso sobre a visibilidade midiática do Grupo Voz - Santos, Julio Cezar Colbeich dos (Universidade do Vale do Rio dos Sinos, 2017)
This research handles the case study of Grupo Voz and Aims to understand the transformations in the process of media visibility of the Voz through the relations and interactions between their religiosity, consumption and materiality in the development of their musical and communicational contents using the virtual ethnography as methodological inspiration. The communicational and artistic contents produced by the band put in place a dialog about the uses of digital communication technologies among the members and transformations occurred in this process. It considers the religious thinking of Voz and its entanglement with aesthetics, pop and the gospel market passed by issues that address the visibility of the group. In a second moment thinks about the trajectory and the Materiality of Communication by virtue of the emergence of bodies in a communication phenomenon that relates performances, aesthetics, art, and transformations developed in the band/media relation. Posteriorly it deals with the consumption issues that surround the empirical object and tensions between beliefs and conflicts with the phonographic market, tactics, strategies and visibility. It culminates with the possibility of a system of visibility and its unfoldings where there are power games between the involved social actors and subjectivities that become important elements in the understanding of the trajectory traversed by the musicians.
Keywords: Visibilidade; Religiosidade; Materialidade da comunicação; Consumo; Visibility; Religiosity; Materiality of Communication; Consumption; ACCNPQ::Ciências Sociais Aplicadas::Comunicação